How to perform AMP? Cubic adjustments for improving the QoE - Montagud, Mario; Boronat, Fernando; Roig, Bernardino; Sapena, Almanzor (Computer communications, 2017)
•Smooth playout adjustment techniques are much more convenient than aggressive ones.•We propose a Cubic Adaptive Media Playout (AMP) strategy to adjust a deviated playout point to a given reference.•Cubic AMP guarantees the smoothness of the playout curve, while keeping the computational complexity low.•Cubic AMP provides better Quality of Experience (QoE) than other existing Linear and Quadratic AMP strategies.•Cubic AMP can be used for different goals (e.g., buffer underflow/overflow avoidance or media synchronization). Adaptive Media Playout (AMP) consists of smoothly and dynamically adjusting the media playout rate to recover from undesired (e.g., buffer overflow/underflow or out-of-sync) situations. The existing AMP solutions are mainly characterized by two main aspects. The first one is their goal (e.g., keeping the buffers’ occupancy into safe ranges or enabling media synchronization). The second one is the criteria that determine the need for triggering the playout adjustments (e.g., buffer fullness or asynchrony levels). This paper instead focuses on a third key aspect, which has not been sufficiently investigated yet: the specific adjustment strategy to be performed. In particular, we propose a novel AMP strategy, called Cubic AMP, which is based on employing a cubic interpolation method to adjust a deviated playout point to a given reference. On the one hand, mathematical analysis and graphical examples show that our proposal provides superior performance than other existing linear and quadratic AMP strategies in terms of the smoothness of the playout curve, while significantly outperforming the quadratic AMP strategy regarding the duration of the adjustment period and without increasing the computational complexity. It has also been proved and discussed that higher-order polynomial interpolation methods are less convenient than cubic ones. On the other hand, the results of subjective tests confirm that our proposal provides better Quality of Experience (QoE) than the other existing AMP strategies. [Display omitted]